Assessment of plant species composition and natural regeneration in abandoned settlements in the lower montane forest of Kilimanjaro National Park, Tanzania. Issue 1 (2nd January 2022) - Kikoti, Imani Abinery; Mligo, Cosmas; Ndangalasi, Henry Joseph
Abstract : Anthropogenic modification of montane forests to other land uses has significant effects on native vegetation and the ecological functions of plant communities, such as in the forests of Mount Kilimanjaro. This study was carried out in Kilimanjaro National Park at the former Engushai forest village, where local people were relocated for conservation in 2006. Forty 20 × 50 m plots were established in areas with different historical land use (former settlement, former cultivation, transition and natural forest). We recorded 132 plant species, representing 114 genera and 58 families. The highest tree species richness was recorded in the forest zone (11 ± 1 per plot), followed by in the transition zone (7 ± 1), former cultivation zone (4 ± 1) and former settlement zone (4 ± 0.4). The natural forest was more diverse in terms of tree species than other sites ( H' = 1.83 ± 0.09, evenness of 0.48 ± 0.02). Analysis of variance showed significant variation in tree species richness, diversity index and evenness among previously disturbed sites and natural forests. The vegetation is at an early stage of succession in anthropogenically impacted areas. However, the domination of Vernonia lasiopus and Bothriocline longipes in the formerly degraded areas was crucial for restoring the microclimate and soil fertility vital for forest development. There is adequate potential for and patterns of natural regeneration of indigenous trees in the anthropogenically impacted areas. The current passive management by Kilimanjaro National Park facilitates forest recovery, indicating the high resilience of these montane forests. It is recommended to monitor the future recovery and succession of the lower montane forest.